Effectiveness of Arm Strength, Leg Strength, and Body Flexibility on Students' Volleyball Underhand Passing Ability - Muhammad Ishak; Budiman Agung Pratama; Davi Sofyan (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
This researcher aims to determine the effect of arm strength, leg strength and body flexibility on underhand passing ability in volleyball. The population in this study were students of SMA Negeri 9 Makassar. A sample of 30 people was taken based on random sampling. The dependent variable of the research is volleyball underhand passing ability. The intervening variable is body flexibility. The independent variables are arm strength and leg strength. The research method is a descriptive method, with a path analysis research design. The research data were analyzed using correlation and regression techniques at a significance level of 95%. The results of the research show that: (1) There is a direct influence of arm strength on body flexibility in students (ß = 0.555 with a significance level of 0.001 < α 0.05). (2) There is a direct influence of leg strength on flexibility in students (ß = 0.407 with a significance level of 0.011 < α 0.05). (3) There is a direct influence of arm strength on underhand passing ability in volleyball among students (ß = 0.343 with a significance level of 0.018 < α 0.05). (4) There is a direct influence of leg strength on underhand passing ability in volleyball among students (ß = 0.266 with a significance level of 0.041 < α 0.05). (5) There is a direct influence of body flexibility on underhand passing ability in volleyball among students (ß = 0.390 with a significance level of 0.011 < α 0.05). (6) There is no influence of arm strength on the ability to pass down in volleyball through body flexibility in students (ß = 0.216 < 0.343). (7) There is no influence of leg strength on underhand passing ability in volleyball through body flexibility in students or a group of students (ß = 0.159 < 0.266).